Gilbert Mixers With Microwave Quadrature/Differential Generators: An Approach for Millimeter-Wave IC - Meng, Chinchun; Tseng, Sheng-Che (My University, 2009)
Several microwave passive components can be integrated with active circuits in standard silicon processes for millimeter-wave applications. Passive components such as Marchand baluns, quadrature couplers, and rat-race hybrids are directly implemented on a standard low-resistivity (similar to 10 Omega xcm) silicon substrate for size compactness because of the high dielectric constant. New circuit design concepts such as balanced path loss and distortionless transmission lines are applied to tolerate the unavoidable loss and to maintain the functionality of components.
Keywords: Down-converter; dual-band; Marchand balun; micromixer; phase inverter; quadrature; rat-race coupler; SiGe BiCMOS; silicon substrate; single-sideband; ultra-wideband; up-converter; wideband